The Modernists - Kotryna Garanasvili (Janeway JS, 2021)
Architecture and literature are significant and distinctive forms of artistic expression demonstrating the traditions and characteristics of their own. However, the relation between them excels the superficial difference in the final form of their creative process. They are interrelated not only by the underlying structure, but also by their ability to generate complex meanings. This interrelation is particularly interesting to explore in the creative process of writing fiction and deliberately focusing on architectural spaces. In my novel, The Modernists, I employ architectural structures to establish and intensify the central themes and literary meanings to test the ways that architecture, urban space and literature can be brought together in fiction. Accompanied by a commentary, the excerpts from the finished novel presents a story told through the prism of architecture. Keywords: architecture, creative writing, interdisciplinary research, semiotics